Peroral Endoscopic Myotomy for Esophageal Achalasia in Portugal: Outcomes of the First Prospective Series - Rui Mendo; Pedro Barreiro; José Rodrigues; Catarina Félix; Catarina O'Neill; Iala Carina; Joyce Chivia; Cristina Chagas (GE: Portuguese Journal of Gastroenterology, 2020)
Background: Peroral endoscopic myotomy (POEM) is an innovative achalasia treatment procedure that involves myotomy of the lower esophageal sphincter through a submucosal tunneling approach, combining the efficacy of surgical myotomy with the benefit of being a less invasive treatment. At this time, no data are available of POEM in Portugal. This study aimed to examine the safety and short-term outcomes of POEM in a Portuguese center. Methods: Fifty POEM were performed on 49 consecutive patients at our institution between January 2017 and January 2020. A prospective study of a consecutive series of patients was conducted, including procedure time, myotomy location and length, adverse events and clinical success. An Eckardt score of ≤3 after POEM was deemed as a successful outcome. Gastroesophageal reflux disease (GERD) was evaluated based on symptoms and on upper endoscopy, which was performed at 3–6 months postoperatively to check for reflux esophagitis. Results: POEM was successfully completed in all cases: 70% (n = 35) were naïve and 30% (n = 15) had previous treatments. The mean procedure time was 73.4 ± 22.6 min (range 45–125 min). There were no major adverse events. Minor adverse events were rare (8%), and there was no perioperative mortality. The Eckardt score significantly decreased from 6.9 ± 2.4 preoperatively to 0.5 ± 1.0 postoperatively (p < 0.05). Overall clinical success was documented in 98, 98 and 95.2% at 1, 3 and 6 months, respectively. These short-term outcomes after POEM were independent of previous treatments. Symptomatic GERD was seen in 22.4% of patients. Conclusions: Our results confirm the safety and excellent short-term efficacy of POEM in a Portuguese center. This supports POEM as one of the first-line achalasia therapies in Portugal when performed by experienced operators.